AKULTURASI ISLAM DENGAN BUDAYA DI PULAU JAWA - Adisty Nurrahmah Laili; Ega Restu Gumelar; Husnul Ulfa; Ranti Sugihartanti; Hisny Fajrussalam (Jurnal Soshum Insentif, 2021)
Abstrak – Islam brought changes in cultural acculturation including tombstones, literary arts, performing arts and carving arts. Besides having a lot of influence in the field of art, Islamic teachings also affect the nature and habits of the people on the island of Java. Acculturation between Islam and culture on the island of Java occurs in many ways, the most visible of which is the work of carving. The occurrence of acculturation between Islamic teachings and Javanese culture does not cause the loss of previous cultural values, but enriches cultural diversity in Indonesia. The process of the entry of Islam into Indonesia has influenced and experienced cultural acculturation with local culture, especially Javanese culture. There are so many results or forms of acculturation between Islamic religious teachings and Javanese culture, starting from the history of the entry of Islam in the archipelago through the services of the Songo guardians and cultural developments from time to time, starting from human civilization in the archipelago, especially the island of Java, the history of the Dutch and Japanese colonial times. , the era of the Hindu-Buddhist kingdoms to the Islamic kingdoms on the island of Java which we can still see its legacy to this day. In writing this study, we discuss examples of the results of acculturation of Javanese culture such as building art, carving art and literary arts with Islamic teachings and the influence of the acculturation results of these two values ​​and cultures. Abstrak – Islam membawa perubahan akulturasi budaya diantaranya pada batu nisan, seni sastra, seni pertunjukan dan seni ukir. Selain banyak mempengaruhi dalam bidang seni ajaran islam juga mempengaruhi sifat serta kebiasaan masyarakat di pulau jawa. Akulturasi antara islam dan kebudayaan di pulau jawa terjadi dalam banyak hal diantaranya yang paling terlihat yaitu hasil karya seni ukir. Terjadinya akulturasi antara ajaran islam dan kebudayaan masyarakat jawa tersebut tidak menyebabkan hilangnya nilai kebudayaan sebelumnya, tetapi memperkaya keanekaragaman budaya di Indonesia. Proses masuknya Islam ke Indonesia telah mempengaruhi serta mengalami akulturasi budaya dengan budaya lokal, khususnya budaya Jawa. Banyak sekali hasil atau wujud akulturasi antara ajaran agama islam dan budaya jawa, berawal dari sejarah masuknya Islam di nusantara melalui jasa para wali songo dan perkembangan budaya dari masa ke masa, mulai dari peradaban manusia di nusantara khususnya pulau jawa, sejarah masa kolonial belanda dan jepang, zaman kerajaan hindu-budha hingga kerajaan-kerajaan islam di pulau jawa yang masih dapat kita lihat peninggalannya sampai saat ini. Pada penulisan penelitian ini membahas tentang contoh hasil akulturasi kebudayaan jawa seperti seni bangunannya, seni ukir dan seni sastra dengan ajaran agama islam serta pengaruh dari hasil akulturasi kedua nilai dan budaya tersebut.